2021
DOI: 10.1016/j.hroo.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of intermittent handheld electrocardiogram and continuous electrocardiogram monitoring with an implantable loop recorder to detect incident and recurrent atrial fibrillation during 1 year after coronary artery bypass graft surgery: A prospective cohort study

Abstract: BACKGROUND Atrial fibrillation (AF) is common after coronary artery bypass graft (CABG) surgery.OBJECTIVE To evaluate the incidence and recurrence rate of AF during 1 year after CABG surgery. We also aimed at calculating the AF burden and compare long-term intermittent vs continuous electrocardiogram (ECG) monitoring.METHODS Forty patients scheduled for CABG surgery were equipped with an implantable loop recorder (ILR). After discharge, they carried out handheld ECG 3 times daily during the first 30 postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Pacing capture from surface electrocardiogram (ECG) monitoring is a common bedside technique [ 9 ], also known as blind insertion, which easily leads to atrial perforation, and the probability of implantation in the best position (right ventricular apex) is only 44%. Blind insertion (ECG monitoring on body surface) and implantation under X-ray cannot judge the degree of contact between the electrode tip and electrode [ 10 , 11 ]. Using these two methods, it is not uncommon for electrodes to insert into the myocardium and penetrate through the atrial or ventricular wall in severe cases.…”
Section: Introductionmentioning
confidence: 99%
“…Pacing capture from surface electrocardiogram (ECG) monitoring is a common bedside technique [ 9 ], also known as blind insertion, which easily leads to atrial perforation, and the probability of implantation in the best position (right ventricular apex) is only 44%. Blind insertion (ECG monitoring on body surface) and implantation under X-ray cannot judge the degree of contact between the electrode tip and electrode [ 10 , 11 ]. Using these two methods, it is not uncommon for electrodes to insert into the myocardium and penetrate through the atrial or ventricular wall in severe cases.…”
Section: Introductionmentioning
confidence: 99%
“…In a study comparing 30-day continuous electrocardiogram monitoring with standard of care, the underreporting of subclinical POAF in cardiac surgery patients was highlighted by a 17.9% absolute difference in AF detection rate . Using continuous cardiac rhythm monitoring, 2 studies demonstrated that both the incidence of POAF and the AF recurrence rate after CABG are most likely underestimated …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, longer ECG monitoring duration may be necessary to increase the chances of detecting AF episodes. Additionally, ECG requires direct contact with electrodes placed on the body, which can be inconvenient for continuous monitoring in everyday settings [38].…”
Section: The Role Of Ecg In Af Detectionmentioning
confidence: 99%